THE CORRELATION BETWEEN THE USE OF TIKTOK BY ENGLISH STUDY PROGRAM STUDENTS FKIP UNIVERSITAS RIAU AND THEIR ACADEMIC PROCRASTINATION - Tri Cahyani, Shalsabilla; Mahdum; Supriusman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examined the correlation between the use of TikTok and academic procrastination among fifth-semester English Study Program students at Universitas Riau. Using a quantitative research design, data were collected from 55 students through the questionnaires by using Procrastination Assessment Scale for Students (PASS) and Social Media Use Scale (SMUS). Statistical analysis using Pearson Product Moment Correlation revealed a strong correlation (ρ = 0.688) with a significance value of p= 0.000 indicating there is a significant positive relationship between the use of TikTok and academic procrastination. These findings showed that when the use of TikTok increases, the level of procrastination also increases. The study recommends that educators can provide guidance on digital well-being and clear deadline also constructive feedback can help to reduce the habit of academic procrastination. In addition, flexible deadlines for more complex assignments are recommended while minimizing procrastination.